“Sieves of Responsibility” – Connecting Failures of Genocide Prevention and Geopolitical Interests to Atrocity in Nagorno-Karabakh - Hackett, David (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
This article aims to contribute to both a legal and practical understanding of how international law dedicated to both genocide prevention and the cessation of genocidal atrocity failed during the 8-month long blockade of the Lachin Corridor – and the ensuing invasion and seizure of Nagorno- Karabakh over a 24-hour period by the Azerbaijani armed forces on 17 September 2024. The invasion led to the forced displacement of nearly the entire territory’s ethnically indigenous Artsakhtsi- Armenian population, amounting to a de facto deportation while escaping the threat of atrocity crimes. Through a discussion of (A) the events that preceded and led to the invasion of Nagorno- Karabakh itself, (B) an analysis of international law on genocide prevention through institutional mechanisms (i.e. UN Convention on the Prevention and Punishment of the Crime of Genocide, 1948) and military intervention (i.e. Responsibility to Protect/R2P doctrine), (C) the difficulties of engaging with these mechanisms at a general level, (D) the international community’s response to the seizure of Nagorno-Karabakh, and (E) the geopolitical conditions surrounding the South Caucasus and Nagorno-Karabakh crisis, this article aims to identify the failures of both legal mechanisms intended to prevent the cleansing of Nagorno-Karabakh and external actors (i.e. Russian peacekeeping forces legally stationed in the territory) to intervene and respond to the invasion in geopolitically turbulent conditions characterized by intersecting state interests.
Keywords: Nagorno-Karabakh